Crystal engineering of a co-crystal of antipyrine and 2-chlorobenzoic acid: relative energetic contributions based on multipolar refinement. Issue 44 (25th October 2022) - Bilal, Aqsa; Mehmood, Arshad; Noureen, Sajida; Lecomte, Claude; Ahmed, Maqsood
Abstract : The growth and stability of a new 1 : 1 antipyrene–dichlorobenzoic acid cocrystal system has been analyzed in terms of electron density analysis and electrostatic interaction energy contributions. Abstract : The growth and stability of a new cocrystal between antipyrine and 2-chlorobenzoic acid (AN –CBA ) is analysed in terms of electrostatic and topological parameters via an experimental and theoretical charge density analysis. The co-crystal is thermally stable up to 140 °C. High-resolution X-ray diffraction data were collected at 100 K to carry out a multipolar refinement based on the multipolar atom model of Hansen and Coppens using the Mopro program. The experimental results are in close agreement with the theoretical values obtained after multipolar refinement using structure factors generated from DFT-D3 single point energy calculations. Strong electrostatic complementarity is found between contributing co-formers. The electron rich pyrazolone ring makes the carbonyl oxygen atom a strong acceptor of a classical hydrogen bond. Electrostatic interaction energies between AN and CBA molecules show one strong contribution of an AN –CBA dimer driving the cocrystallization and dictating the orientation of the coformers in the cocrystal. In general, the heterodimers between AN –CBA are more stable than the dimers between pure fragments. The topological analysis of intermolecular interactions shows that in addition to the single O–H⋯O hydrogen bond between AN and CBA, a large number of C–H⋯O and O–H⋯π type van der Waals interactions support the assembly. This study highlights the significance of using electrostatics to discuss the stability of crystalline solid forms of pharmaceutical cocrystals.